Evaluating New Extension Agent Communication Training Effectiveness to Prepare Agricultural and Environmental Communicators for Global Issues - Jessica A. Holt; Arthur Leal; Angela Hurt (Journal of International Agricultural and Extension Education, 2019)
Extension agents are a valuable source of information within their communities throughout the world. Tasked with sharing research-based information from the universities and serving as the land-grant university within their communities, agents are the face and voice of the university on daily basis. However, this research sought to determine how confident new agents in Georgia were in their ability to effectively communicate within their communities before and after attending a communication workshop. Using a retrospective pre- and post-test survey, the results indicated the agents were most confident in their abilities create high-quality promotional videos and write Public Service Announcements for radio after the training. The results indicated agents were least confident in their abilities to utilize the Extension data base and write effectively. Overall, the results indicated in increase in agents’ perceived ability to effectively communicate in their communities after attending the training. Additionally, the results provide direction for future training and workshops to better prepare agents to effectively communicate information from land-grant universities to their communities and the world.
Keywords: communication training; research-based communication; Extension agent workshop; Extension communication